Clinical Outcomes in Patients With Left Bundle Branch Area Pacing vs. Right Ventricular Pacing for Atrioventricular Block - Li, Xiaofei; Zhang, Junmeng; Qiu, Chunguang; Wang, Zhao; Li, Hui; Pang, Kunjing; Yao, Yan; Liu, Zhimin; Xie, Ruiqin; Chen, Yangxin; Wu, Yongquan; Fan, Xiaohan (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background: Left bundle branch area pacing (LBBAP) is a novel pacing modality with stable pacing parameters and a narrow-paced QRS duration. We compared heart failure (HF) hospitalization events and echocardiographic measures between LBBAP and right ventricular pacing (RVP) in patients with atrioventricular block (AVB). Methods and Results This multicenter observational study prospectively recruited consecutive AVB patients requiring ventricular pacing in five centers if they received LBBAP or RVP and had left ventricular ejection fraction (LVEF) >50%. Data on electrocardiogram, pacing parameters, echocardiographic measurements, device complications, and clinical outcomes were collected at baseline and during follow-up. The primary outcome was first episode hospitalization for HF or upgrade to biventricular pacing. LBBAP was successful in 235 of 246 patients (95.5%), while 120 patients received RVP. During a mean of 11.4±2.7 months of follow-up, the ventricular pacing burden was comparable (83.9±35.1% vs. 85.7±30.0%), while the mean LVEF differed significantly (62.6±4.6% vs. 57.8±11.4%) between the LBBAP and RVP groups. Patients with LBBAP had significantly lower occurrences of HF hospitalization and upgrading to biventricular pacing than patients with RVP (2.6% vs. 10.8%, p<0.001), and the differences in primary outcome between LBBAP and RVP were mainly observed in patients with ventricular pacing >40% or with baseline LVEF<60%. The primary outcome was independently associated with LBBAP (adjusted HR 0.14, 95% CI: 0.04-0.55), previous myocardial infarction (adjusted HR 6.82, 95% CI: 1.23-37.5) and baseline LVEF (adjusted HR 0.91, 95% CI: 0.86-0.96). Conclusion Permanent LBBAP might reduce the risk of HF hospitalization or upgrade to biventricular pacing compared with RVP in AVB patients requiring a high burden of ventricular pacing. Clinical Trial Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT03851315; URL: http://www.chictr.org.cn; Unique Identifier： ChiCTR2100043296.